ASSESSMENT OF HUMAN RESOURCE MANAGEMENT PERFORMANCE IN HIGHER EDUCATION WITH INFORMATION SYSTEMS - Muhammad Ridwan; Sitti Rizky Mulyani; Rio Andhika Putra; Hanna Pratiwi; Vicky Brama Kumbara (Jurnal Ipteks Terapan, 2023)
Human resources (HR), consisting of teaching staff and supporting staff in tertiary institutions, are in a very strategic position because they have a direct influence on the learning process, the quality of degrees and competitive product models. The effectiveness of actions in the teaching and learning process and improving the academic atmosphere are strongly influenced by quality standardization and quality assurance that are appropriate for universities to implement, one of which is human resources (HR). . The prerequisite for the correct implementation of higher education personal quality assurance is the existence of an accurate database that can be used in every decision-making process. Therefore, an information system must be developed to ensure the quality of higher education human resources. This personal quality assurance information system can work to facilitate higher education quality assurance, so that the quality assurance process can be carried out through networks and databases, management information systems and integrated support. decision support system. The stages of this information system design include requirements analysis, process modeling design, software requirements analysis and design